Sarcoma metastasis to the pancreas: experience at a single institution - Miseon Lee; Joon Seon Song; Seung-Mo Hong; Se Jin Jang; Jihun Kim; Ki Byung Song; Jae Hoon Lee; Kyung-Ja Cho (Korean Society of Pathologists & the Korean Society for Cytopathology, 2020)
Background Reports of metastatic sarcoma to the pancreas are limited. We reviewed the clinicopathologic characteristics of such cases. Methods We reviewed 124 cases of metastatic tumors to the pancreas diagnosed at Asan Medical Center between 2000 and 2017. Results Metastatic tumors to the pancreas consisted of 111 carcinomas (89.5%), 12 sarcomas (9.6%), and one melanoma (0.8%). Primary sarcoma sites were bone (n=4); brain, lung, and soft tissue (n=2 for each); and the uterus and pulmonary vein (n=1 for each). Pathologically, the 12 sarcomas comprised 2 World Health Organization grade III solitary fibrous tumors/hemangiopericytomas, and one case each of synovial sarcoma, malignant solitary fibrous tumor, undifferentiated pleomorphic sarcoma, osteosarcoma, mesenchymal chondrosarcoma, intimal sarcoma, myxofibrosarcoma, myxoid liposarcoma, rhabdomyosarcoma, subtype uncertain, and high-grade spindle-cell sarcoma of uncertain type. The median interval between primary cancer diagnosis and pancreatic metastasis was 28.5 months. One case manifested as a solitary pancreatic osteosarcoma metastasis 15 months prior to detection of osteosarcoma in the femur and was initially misdiagnosed as sarcomatoid carcinoma of the pancreas. Conclusions The metastatic sarcoma should remain a differential diagnosis when spindle-cell malignancy is found in the pancreas, even for solitary lesions or in patients without prior history.